(untitled) (Journal of Dhaka National Medical College & Hospital, 2021)
Background: Migraine is the most common cause of headaches that are responsible for different kinds of disabilities. There will be loss of work due to disabilities. This was an effort to obtain such information regarding the level of disabilities due to migraine. Materials and Methods: The current study was cross-sectional type of descriptive observational study conducted from 1st June, 2017 to 30th may 2018. The study included the patients attending at Neurology Outpatient Department of Dhaka National Medical Institute Hospital. Data were collected by face-to-face interview. Collected data were computed and analyzed. Results: Mean age of respondents 29.9 years with SD 14.28 ranging from 9.16 to 62.58 years. Among them about two-thirds (64%) of the respondents were female. More than one-third of the respondents (42%) were students. More than two-third of the respondents (68%) had interruption during sleep. More than two-third of the respondents (68%) felt pain for 2-3 hours. More than one-third of the respondents (34%) were overweight or obese. More than half (52%) of the respondents had severe disability. Conclusion: Most of respondents were female and were students. They had impairment in their function and found severe disabilities. So, there was no scope to treat migraine as a simple way. J. Dhaka National Med. Coll. Hos. 2021; 27 (01): 24-27